Impact of Hypothermia Initiation and Duration on Perihemorrhagic Edema Evolution After Intracerebral Hemorrhage - Volbers, Bastian; Herrmann, Sabrina; Willfarth, Wolfgang; Lücking, Hannes; Kloska, Stephan; Dörfler, Arnd; Huttner, Hagen; Kuramatsu, Joji; Schwab, Stefan; Staykov, Dimitre (Stroke, 2016)
Intracerebral hemorrhage (ICH) causes high morbidity and mortality. Recently, perihemorrhagic edema (PHE) has been suggested as an important prognostic factor. Therapeutic hypothermia may be a promising therapeutic option to treat PHE. However, no data exist about the optimal timing and duration of therapeutic hypothermia in ICH. We examined the impact of therapeutic hypothermia timing and duration on PHE evolution.In this retrospective, single-center, case-control study, we identified patients with ICH treated with mild endovascular hypothermia (target temperature 35°C) from our institutional database. Patients were grouped according to hypothermia initiation (early: days 1-2 and late: days 4-5 after admission) and hypothermia duration (short: 4-8 days and long: 9-15 days). Patients with ICH matched for ICH volume, age, ICH localization, and intraventricular hemorrhage were identified as controls. Relative PHE, temperature, and intracranial pressure course were analyzed. Clinical outcome on day 90 was assessed using the modified Rankin scale (0-3=favorable and 4-6=poor).Thirty-three patients with ICH treated with hypothermia and 37 control patients were included. Early hypothermia initiation led to relative PHE decrease between admission and day 3, whereas median relative PHE increased in control patients (-0.05 [interquartile range, -0.4 to 0.07] and 0.07 [interquartile range, -0.07 to 0.26], respectively; P=0.007) and patients with late hypothermia initiation (0.22 [interquartile range 0.12-0.27]; P=0.037). After day 3, relative PHE increased in all groups without difference. Outcome was not different between patients treated with hypothermia and controls.Early hypothermia initiation after ICH onset seems to have an important impact on PHE evolution, whereas our data suggest only limited impact later than day 3 after onset.
EVALuna2:22477

Impact of Perihemorrhagic Edema on Short-Term Outcome After Intracerebral Hemorrhage - Volbers, Bastian; Willfarth, Wolfgang; Schwab, Sibylle; Kuramatsu, J. B.; Huttner, Hagen; Struffert, Tobias; Dörfler, Arnd; Staykov, S. (Neurocritical Care, 2016)
Intracerebral hemorrhage (ICH) is a devastating disease with ICH volume being the main predictor of poor outcome. The prognostic role of perihemorrhagic edema (PHE) is still unclear; however, available data are mainly derived from analyses during the first days after symptom onset. As PHE growth may continue up to 14 days after ICH, we evaluated PHE over a longer period of time and investigated its impact on short-term clinical outcome.In this monocentric retrospective cohort study, patients with spontaneous supratentorial ICH were identified from our institutional data base. Different time points of CT scans were merged to time clusters for better comparison (day 1, 2-3, 4-6, 7-9, 10-12). Absolute volumes of ICH and PHE were obtained using a validated semiautomatic volumetric algorithm. Clinical outcome at discharge was assessed using the modified Rankin Scale (0-3 = favorable, 4-6 = poor).220 patients (83 with favorable, 137 with poor outcome) were included in the final analysis. Mean ICH volume on admission was 22.8 [standard deviation (SD) 24.6] cm(3). Mean absolute PHE volume on admission was 22.5 (SD 20.8) cm(3) and increased to a mean peak volume of 38.1 (SD 31.4) cm(3) during 6.7 (SD 4.1) days on average. Besides GCS on admission, functional status before ICH, peak hematoma volume, lobar localization and fever burden, and high peak PHE volume predicted poor outcome at discharge [OR 0.977 (95 % CI 0.957-0.998)] in the multivariable analysis.PHE may have a negative impact on short-term functional outcome after ICH and therefore represent a possible treatment target.
EVALuna2:22273

Intraventricular fibrinolysis does not increase perihemorrhagic edema after intracerebral hemorrhage - Volbers, Bastian; Wagner, Irina; Willfarth, Wolfgang; Dörfler, Arnd; Schwab, Stefan; Staykov, Dimitre (Stroke, 2013)
BACKGROUND AND PURPOSE - : Additional intraventricular hemorrhage leads to higher mortality and worse functional outcome after intracerebral hemorrhage (ICH). Intraventricular fibrinolysis (IVF) with recombinant tissue plasminogen activator (rtPA) is an emerging treatment strategy for such patients. However, experimental studies suggest that rtPA may exert proedematous effects and lead to increased perihemorrhagic edema (PHE) after ICH. We aimed to compare the course of PHE after ICH between patients who received IVF with rtPA and controls matched for ICH volume. METHODS - : Patients were identified retrospectively from our institutional ICH database. Sixty-four patients with ICH and intraventricular hemorrhage who were treated with IVF were compared with 64 controls, who did not receive IVF, matched for ICH volume. The course of PHE was assessed on computed tomography scans (day 1, days 2 and 3, days 4-6, 7-9, and 10-12) using a threshold-based semiautomatic volumetric algorithm. Relative PHE was calculated as a ratio of PHE volume and initial ICH volume. RESULTS - : The matching algorithm resulted in similar mean ICH volumes in both groups (20.01±17.5 mL, IVF vs 20.08±17.1 mL, control). Intraventricular hemorrhage volume was larger in the IVF group (26.8±19.2 mL vs 9.2±13.4 mL). The mean total rtPA dose used for IVF was 8±6 mg. PHE increased over time in both groups until day 12. At all investigated time points, there was no significant difference in relative PHE between the IVF group and controls (F=0.39; P=0.844). CONCLUSIONS - : IVF with rtPA did not lead to a relevant increase in PHE after ICH. rtPA doses used in the current study seem to be safe regarding PHE. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: intracerebral hemorrhage; intraventricular fibrinolysis; intraventricular hemorrhage; perihemorrhagicedema; recombinant tissue-type plasminogen activator; semiautomatic volumetry; X-ray computed tomography